2018
DOI: 10.1097/igc.0000000000001366
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pathologic Chemotherapy Response Score in Patients With Ovarian Cancer After Neoadjuvant Chemotherapy

Abstract: ObjectivesThe aim of the study was to investigate the correlation of chemotherapy response score (CRS) after neoadjuvant chemotherapy (NACT) to treatment outcomes in ovarian cancer (OC).MethodsChemotherapy response score was retrospectively determined on pathology slides of all patients with epithelial OC that had interval debulking surgery (IDS) between 2009–2014. Chemotherapy response score 1 was given when tumor was present and infiltrated by inflammatory cells, CRS 2 when both tumor and regressive chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
5
16
0
Order By: Relevance
“…Although the diameter of metastatic tumors could be reduced using NACT, even to less than 1 cm, the residual tumor tissue may contain cancer stem cells responsible for chemoresistant recurrence [20, 27, 30]. It has been reported that a small subset (5 to 12%) of patients show pathologic complete response (pCR) with no residual tumor cells after NACT and excellent prognosis [31, 32]. Hence, the crucial goal for NACT is to achieve no residual tumor after IDS or even pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diameter of metastatic tumors could be reduced using NACT, even to less than 1 cm, the residual tumor tissue may contain cancer stem cells responsible for chemoresistant recurrence [20, 27, 30]. It has been reported that a small subset (5 to 12%) of patients show pathologic complete response (pCR) with no residual tumor cells after NACT and excellent prognosis [31, 32]. Hence, the crucial goal for NACT is to achieve no residual tumor after IDS or even pCR.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been validated, by other groups, as an effective approach in predicting progression-free survival and platinum sensitivity, but data on overall survival are conflicting 7. Moreover, the efficacy of this score in predicting different outcomes has been tested in women with any clinical response to neoadjuvant chemotherapy, including patients with no pathologic response and thus worse survival 8 9…”
Section: Introductionmentioning
confidence: 99%
“…The 3 tier CRS system was proposed in 2015 and recently recommended by ICCR and CAP in ovarian cancer pathology reporting guidelines [3,7]. Subsequently, several studies have further examined this system and correlated it with prognosis [4,[8][9][10][11][12][13][14]. However, these results showed variable prognostic value, particularly in scoring adnexal samples [8,10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several studies have further examined this system and correlated it with prognosis [4,[8][9][10][11][12][13][14]. However, these results showed variable prognostic value, particularly in scoring adnexal samples [8,10,[12][13][14]. Most studies showed consistent results when using modified 2 tier CRS as compared to the 3 tier CRS in the predicting PFS based on omental tumor sample, while these studies yield conflicting results when using 2 tier or 3 tier CRS predicting OS or using adnexal tumor sample [4,[8][9][10][11][12]14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation